The Role of Islam in Affecting the Transformation of Traditional Agriculture Knowledge: A Systematic Review of Dewi Sri Literature - Imamah, Fardan Mahmudatul; Dewantri, Puja Alviana; Lin, Yuqiong (Yayasan Irwan Abdullah Cendekia, 2024)
This research aims to comprehensively understand how Islam has influenced the fundamental discussions within the Islamic Environmentalism movement, explicitly concerning agriculture and traditional knowledge systems. The study analyzed 103 scholarly articles and publications from Google Scholar, covering the period from 2011 to 2023. The search was conducted on December 14, 2023, using the keyword 'Dewi Sri.' The results show that cultural and agricultural factors specific to the region influence the Javanese agroecological perspective. In contrast, Islamic agroecological methods are shaped by the integration of Islamic teachings, particularly the concept of Green Islam, to create food systems that are both sustainable and self-regulating. However, the specific mechanism by which Islam affected alterations in traditional agricultural knowledge systems cannot be well elucidated using broad terms. It is essential to acknowledge that understanding the role of Islam in influencing the transformation of traditional agriculture knowledge in the Islamic environmentalism movement can facilitate collaboration within the Muslim community. This fact can serve as a valuable resource for integrating Javanese values without posing a threat to the integrity of Islam but instead as an opportunity to demonstrate that Islam also shares the same commitment to environmental preservation.